Differences in the Perceptions of Moral Intensity in the Moral Decision Process: An Empirical Examination of Accounting Students - Leitsch, Deborah L. (Journal of business ethics, 2004)
The purpose of this study was to gain a better understanding of the impact of moral issues on the moral decision-making process within the field of accounting. In particular, the study examined differences in the perceptions of the underlying characteristics of moral issues on the specific steps of the moral decision-making process of four different accounting situations., The research results suggested that student's perception of the components of moral intensity as well as the various stages of the moral decision-making process was influenced by the type and intensity of the moral issue. In general, accounting student's perceptions of the importance of these variables varied between less unethical and more unethical accounting issues. The differences in perceptions of four moral intensity components: magnitude of consequences, concentration of effect, probability of effect and proximity stood out more in the accounting issues analyzed., The findings presented in this research extend the existing understanding about the importance of the components of moral intensity in the ethical decision-making process of accounting processionals. The results can be integrated into revised or newly adopted company codes of ethics to comply with the requirements of the newly enacted Sarbones-Oxley Act of 2002. They can also be used to enhance ethics coursework and training programs in educational settings and industry.